Protein enrichment through synergistic activities of fruit wastes using white rot fungi under submerged state fermentation - Jamal, Parveen; Saheed, Olorunnisola Kola; Alam, Md Zahangir; Muyibi, Suleyman Aremu; Abdul Karim, Mohamed Ismail (Journal of Pure and Applied Microbiology, 2014)
In order to measure the suitability of microbes and substrate composites for animal feed supplements, submerged state bioconversion (SmB)was performed. Chemical analysis of all selected substrates showed high fermentable sugar which can support microbial growth. Selected microbes Phanerochaetechrysosporium (P. chrysosporium), Panustigrinus(M6) and RO2 were grown on sole liquid and solid substrates and their respective composites. Protein content of substrate increased over 127 times on sole liquid substrates and 216 times on solid.Additively, all selected strain showed improved protein synthesis on solid sole substrate with RO2 leading with 49.23 mg/g. Protein content of biomass increased in composite substrates with P. chrysosporium synthesizing its highest protein (18.59 mg/g) on solid mixture of all selected substrate whereas banana peel and pineapple peel composite (BpPin) was best for M6 (22.97 mg/g) and RO2 (26.34 mg/g) respectively.